1990
DOI: 10.1111/j.1528-1167.1990.tb06305.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Postictal Psychosis: A Stereo EEG Study

Abstract: An acute psychosis characterized by auditory hallucinations and paranoid delusions developed in a 19-year-old man with temporal lobe epilepsy after he had a cluster of seizures when antiepileptic drugs (AEDs) had been gradually discontinued. Continuous sterotactic depth and epidural EEG recordings confirmed that this was a postictal rather than an ictal event. Acute postictal psychosis is a self-limited condition phenomenologically distinct from ictal or postictal confusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 10 publications
5
33
0
3
Order By: Relevance
“…Although there were common features in some of these patients, no generalisations can be made regarding symptoms. Three patients had depressive delusions and hallucinations (1, 2 and 4) and non-specific psychosis (2,3,4). Two patients had nuclear syndromes, paranoid delusions and delusional moods (2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Although there were common features in some of these patients, no generalisations can be made regarding symptoms. Three patients had depressive delusions and hallucinations (1, 2 and 4) and non-specific psychosis (2,3,4). Two patients had nuclear syndromes, paranoid delusions and delusional moods (2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Episodes of postictal psychosis can evolve from a period of postictal confusion or they may emerge from lucid states (20). In either case, they tend to follow a psychosis-free interval of several hours up to a few days after a seizure or, usually, a cluster of complex partial seizures with or without secondary generalization (21)(22)(23)(24).…”
Section: Periictal Violencementioning
confidence: 99%
“…Rare depth electrode studies have shown increased temporal lobe spiking, which has not been confirmed by subsequent studies. 8 An interesting correlation has been noted between postictal psychosis and bilateral independent interictal and ictal foci, validating the need for a repeat study in cases of patients with postictal psychosis and only unilateral focus on long-term monitoring. 9 Forty percent of patients showed new-onset intermittent frontal delta activity during postictal psychosis in a study by Kanner et al 9 DC exhibited EEG findings of insomnia with loss of sleep architecture and gradual resolution of diffuse background slowing.…”
Section: Discussionmentioning
confidence: 94%